The influence of maleyl-lysine and maleyl-methionine on body growth, body composition and wool growth of Merino lambs - Bonifacino, L. A.(Luis Alberto) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1979.